Sorghum phenolic extracts : their storage stability and antioxidant activity in sunflower oil - Duodu, Kwaku Gyebi (University of Pretoria, 2013)
Dissertation (MSc(Agric) Food Science and Technology)--University of Pretoria, 2008.